Crosstalk between protein post-translational modifications and phase separation - Yang Liu; Wenjuan Feng; Yunshan Wang; Bin Wu (Cell Communication and Signaling, 2024)
Abstract The phenomenon of phase separation is quite common in cells, and it is involved in multiple processes of life activities. However, the current research on the correlation between protein modifications and phase separation and the interference with the tendency of phase separation has some limitations. Here we focus on several post-translational modifications of proteins, including protein phosphorylation modification at multiple sites, methylation modification, acetylation modification, ubiquitination modification, SUMOylation modification, etc., which regulate the formation of phase separation and the stability of phase separation structure through multivalent interactions. This regulatory role is closely related to the development of neurodegenerative diseases, tumors, viral infections, and other diseases, and also plays essential functions in environmental stress, DNA damage repair, transcriptional regulation, signal transduction, and cell homeostasis of living organisms, which provides an idea to explore the interaction between novel protein post-translational modifications and phase separation. Video Abstract